Post-Wall German Cinema and National History : Utopianism and Dissent. - O'Brien, Mary-Elizabeth (Studies in German Literature Linguistics and Culture, 113., 2012)
Since unification, a radical shift has occurred in Germans' view of their country's past, with 1989 replacing 1945 as the primary caesura. Events of the cold-war period are seen as decisive in a history that unites yet divides East and West. Establishing foundational myths and finding common experience is pivotal in constructing national identity, and the cinema provides a forum for consumption, negotiation, and contestation of such notions. This book looks at history films made since 1989, exploring how utopianism and political dissent have shaped German identity. At issue is the extent to wh.